Analisis Faktor Penyebab Menurunnya Resiliensi Akademik Pada Siswa MTsN - Rahmadani, Atika; Daulay, Nurussakinah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This research is aimed at the importance of students having academic resilience in helping their educational success. This study used a descriptive quantitative research design. For the collection of respondents, the proportionate stratified random sampling method was used so that 187 class IX students were obtained with 17 representative students per class. The instrument used in this study is the resilience scale, which is adapted from several aspects of resilience described by Reivich and Shatte (2002) (in Nashori & Saputro, 2021). Based on the results of the analysis in the field, it was found that there was a decrease in student academic resilience. The results of the research conducted the factor that most influences the decline in student academic resilience is unstable emotion regulation in students.